The role of structural and electronic factors in shaping the ambipolar properties of donor–acceptor polymers of thiophene and benzothiadiazole1. Issue 94 (14th October 2015) - Ledwon, Przemyslaw; Thomson, Neil; Angioni, Enrico; Findlay, Neil J.; Skabara, Peter J.; Domagala, Wojciech
<x xml:space="preserve">Abstract</x> p- and n-doped states of thiophene-benzothiadiazole based donor–acceptor π-conjugated polymer materials are studied. Results reveal that mesomeric factors mainly influence p-doping, while steric factors account for n-doping peculiarities.